Genetic distance and diversity of breadfruit (Artocarpus altilis) based on morphological characters in Bawean Island, Indonesia - Wardatur Rahmah; Budi Waluyo (Society for Indonesian Biodiversity, 2019)
Abstract. Rahmah W, Waluyo B. 2019. Genetic distance and diversity of breadfruit (Artocarpus altilis) based on morphological characters in Bawean Island, Indonesia. Biodiversitas 20: 3284-3291.  One of the ways to preserve species germplasm is by identifying the genetic distance and intraspecific diversity. The aims of this study were to study the distribution and cultivation status, genetic distance, and diversity of breadfruit plants, Artocarpus altilis (Parkinson ex F.A.Zorn) Fosberg, in Bawean Island, Gresik, Indonesia based on morphological characters. The study made 30 accessions of breadfruit plants spread throughout Bawean Island, which were found to be neither cultivated intensively nor used optimally by the inhabitants. The genetic distance showed that breadfruit in Bawean Island was clustered into 6 groups with similarity coefficient of around 0.9984 to 0.9999. The diversity index value of 1.48 indicated medium diversity of breadfruit on this island.